PENTINGNYA REAKTUKISASI KAJIAN PANCASILA SEBAGAI IDEOLOGI NEGARA DI ERA DIGITAL - Alfred Benu; Maria A. Laot a; Resmananda V. Pian; Chatrine S. Naitboho; Veronika P. Sita; Maria Elise G. Tey Se’ee (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Title in English. The digital era presents a rapid flow of information and global cultural influences that potentially weaken the understanding and application of national values. The re-actualization of Pancasila is a strategic step to ensure that the state ideology remains relevant and functions as a moral guide in modern society. This study emphasizes the importance of presenting Pancasila values in a contextual and easily understandable manner through value-based digital literacy, creative digital media utilization, and the application of ethical media practices. The strategy also includes strengthening cross-sector collaboration, integrating Pancasila-based projects in education and communities, and adapting Pancasila values to contemporary issues such as equality, digital rights, and environmental sustainability. The findings indicate that this approach can help society understand, internalize, and practically apply Pancasila values, keeping the state ideology alive, relevant, and adaptive to social, cultural, and technological challenges in the digital era. This study confirms that strengthening Pancasila-based digital literacy not only preserves national values but also fosters a critical, participatory, and responsible society amid global dynamics.